Molecular pathology of lymphoma and its treatment strategies: from mechanistic elucidation to precision medicine - Wang, Zhongyu; Feng, Shuai; Yao, Xiangmei; Zhao, Renbin; Li, Yujin; Zheng, Maofeng; Li, Zengzheng; Wang, Yajie (Frontiers in Immunology, 2025)
Lymphoma is a highly heterogeneous hematologic malignancy characterized by intricate molecular and pathological mechanisms. Key mechanisms contributing to its complexity include malignant clonal evolution driven by somatic mutations, epigenetic modifications affecting gene regulation and cellular behavior, and dynamic tumor microenvironment remodeling. These factors collectively undermine the efficacy of conventional therapeutic strategies. Differences in the molecular mechanisms of different subtypes lead to heterogeneity in treatment response and recurrence of drug resistance. Current and future investigative priorities emphasize molecular stratification, precision diagnosis and therapeutic strategies, advancement of novel diagnostic tools, and the implementation of artificial intelligence (AI) for integrative analysis of high-dimensional biological data. Moreover, emerging areas such as microbiome-targeted interventions are being explored to improve clinical outcomes and support the evolution of precision oncology in lymphoma treatment.